Digital Marketing Communication of Entrepreneurship Curriculum in Islamic Boarding School: Case Study in Pesantren Sirojul Huda Bandung Regency West Java - Rachmawati, Indri; Pratama Putra, Raditya; Junita Triwardhani, Ike (Institut Komunikasi dan Bisnis LSPR, 2024)
Entrepreneurship is a program that continues to receive significant support. In 2020, the Governor of West Java allocated hundreds of billions of rupiah to foster new entrepreneurs as part of the post-pandemic economic recovery. In Islam, trading (entrepreneurship) holds a prominent position, as highlighted in a hadith narrated by Ahmad, where the Prophet Muhammad (SAW) said,